2010
DOI: 10.1093/brain/awq212
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging markers of Parkinson’s disease nigrostriatal signature

Abstract: One objective of modern neuroimaging is to identify markers that can aid in diagnosis, disease progression monitoring and long-term drug impact analysis. In this study, Parkinson-associated physiopathological modifications were characterized in six subcortical structures by simultaneously measuring quantitative magnetic resonance parameters sensitive to complementary tissue characteristics (i.e. volume atrophy, iron deposition and microstructural damage). Thirty patients with Parkinson's disease and 22 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
323
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(367 citation statements)
references
References 58 publications
37
323
3
4
Order By: Relevance
“…73 A multimodal magnetic resonance imaging study of subcortical gray matter structures using 3-T MRI with T2*-weighted, whole-brain T1-weighted and diffusion tensor imaging scans was recently reported in 30 patients with PD and 22 controls. 74 Patients with PD displayed significantly higher R2* values in the substantia nigra (in keeping with the report of Martin et al), lower fractional anisotropy values in the substantia nigra and thalamus, and higher mean diffusivity values in the thalamus. Voxel-based analyses confirmed these results and, in addition, showed a significant difference in the mean diffusivity in the striatum.…”
Section: Assessment Of Disease Progression With Positron Emission Tomsupporting
confidence: 89%
“…73 A multimodal magnetic resonance imaging study of subcortical gray matter structures using 3-T MRI with T2*-weighted, whole-brain T1-weighted and diffusion tensor imaging scans was recently reported in 30 patients with PD and 22 controls. 74 Patients with PD displayed significantly higher R2* values in the substantia nigra (in keeping with the report of Martin et al), lower fractional anisotropy values in the substantia nigra and thalamus, and higher mean diffusivity values in the thalamus. Voxel-based analyses confirmed these results and, in addition, showed a significant difference in the mean diffusivity in the striatum.…”
Section: Assessment Of Disease Progression With Positron Emission Tomsupporting
confidence: 89%
“…Two other studies 10,26 did find reduced FA in SN correlated with disease severity. Studies focusing on the SN and integrating T2* 20,24 or volumetric analysis 15 with DTI reported that this improved their ability to discriminate patients with PD from healthy controls. There is evidence suggesting that neurodegenerative changes occur outside the SN.…”
Section: Resultsmentioning
confidence: 99%
“…3 A combination of measures of iron content with changes in fractional anisotropy in the substantia nigra resulted in better separation of patients with Parkinson's disease from control individuals compared with each technique separately, with 95% global accuracy. 4 Reduced connectivity of the substantia nigra with the striatum and thalamus was also evidenced in patients with Parkinson's disease using tractography-based methods 5 and resting-state functional connectivity (figure 2). Novel MRI techniques might be helpful for differentiation between Parkinson's disease and atypical parkinsonism (table 1).…”
Section: Imaging For Diagnosis Of Parkinson's Diseasementioning
confidence: 97%